Psychological therapies for people with borderline personality disorder - Storebø, Ole Jakob; Stoffers-Winterling, Jutta M.; Völlm, Birgit A.; Kongerslev, Mickey T.; Mattivi, Jessica T.; Kielsholm, Maja Laerke; Nielsen, Signe Sofie; Jørgensen, Mie Poulsgaard; Faltinsen, Erlend G.; Lieb, Klaus; Simonsen, Erik (Wiley, 2018)
This is a protocol for a Cochrane Review (Intervention). The objectives are as follows: To assess the beneficial and harmful effects of psychological therapies for people with borderline personality disorder (BPD).